2010
DOI: 10.1159/000282668
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect of Commercial Desensitizing Toothpastes on Bovine Enamel Erosion in vitro

Abstract: This study evaluated in vitro commercial desensitizing toothpastes with respect to the prevention of erosion and explored the effect of their agents alone or in combination with fluoride. Bovine enamel blocks were randomly allocated to five groups of 20 and exposed to: Sensodyne ProNamel (1,425 ppm F as NaF, 5% KNO3), Sensodyne Original (no fluoride, 10% SrCl2), Colgate Sensitive (1,450 ppm F as sodium monofluorophosphate, 5% K citrate), Crest (fluoride-only toothpaste, 1,100 ppm F as NaF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 48 publications
1
40
0
8
Order By: Relevance
“…Thus, it is very important to carefully analyse the experimental design and the response variables used in different studies before making any inferences regarding their potential clinical effects. 14 The group in which Colgate Sensitive Pro Relief was used showed lower loss of hardness and enamel wear values, and this can be attributed to some of its components, such as arginine, calcium carbonate, sodium monofluorophosphate and titanium dioxide. This is a pioneer study involving the use of arginine, calcium carbonate and fluoride to inhibit the erosive effect on enamel.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Thus, it is very important to carefully analyse the experimental design and the response variables used in different studies before making any inferences regarding their potential clinical effects. 14 The group in which Colgate Sensitive Pro Relief was used showed lower loss of hardness and enamel wear values, and this can be attributed to some of its components, such as arginine, calcium carbonate, sodium monofluorophosphate and titanium dioxide. This is a pioneer study involving the use of arginine, calcium carbonate and fluoride to inhibit the erosive effect on enamel.…”
Section: Discussionmentioning
confidence: 98%
“…This method has been used in numerous other studies on dental hard tissue wear due to erosion. 17,18 The in vitro model used has been successfully applied to evaluate strategies for preventing dental erosion, 14 as it allows discrimination between different treatments. According to the present design, slurries of the products were applied on the enamel surfaces for 1 minute, a condition that more closely resembles the clinical situation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the combination of NaF with the desensitizing agent KNO 3 impairs the effect of fluoride on the reduction of wear. 37 It is important to bear in mind that other factors such as pH, consistency and abrasivity may modulate the effect of fluoride dentifrices on dental erosion and abrasion. In a recent study it was shown that fluoride concentration and consistency influenced enamel and dentin wear, while the pH seemed to have no effect, 38 as had been previously shown for commercial dentifrices with pH ranging between 4 and 7.…”
mentioning
confidence: 99%
“…2,37,43 This may be due to the interaction between NaF and KNO 3 , which reduces the bioavailability of fluoride. 37 Remineralizing agents, such as hydroxyapatite (with or without F) and Zn-carbonate hydroxyapatite, are expected to induce some mineral precipitation on enamel. 44 However, the incorporation of new hydroxyapatite into demineralized enamel is 30% reduction in wear when compared with a placebo).…”
mentioning
confidence: 99%